The housing evolution of Braga between late antiquity and the early meddle ages - Martins, Manuela (2016)
The study of the domestic architecture evolution in Late Antiquity performs a fairly recent research subject within Hispanic historiography and represents one of the most significant results emerging from urban archaeology that has uncovered a relevant and innovative group of data related with the occupation of cities with Roman foundation between the fourth and eight centuries. In Braga the excavations conducted since 1976 identified remains of several domus that have been the object of systematic research studies in the past decade.2 In reality, the vast majority of the city Late Antiquity occupation continued to privilege areas where the previous domus of High Empire foundation were located. They were object of important reforms between the late third/early fourth centuries in a time when Bracara Augusta was elevated to capital of the new Callaecia province and endured an important urban renovation.